A ratiometric sensor for DNA based on a dual emission Ru(dppz) light-switch complex. Issue 18 (21st April 2017) - Walker, Michael G.; Ramu, Vadde; Meijer, Anthony J. H. M.; Das, Amitava; Thomas, Jim A.
Abstract : Herein we describe the DNA binding properties of two new water-soluble ruthenium complexes; experimental and computational data reveal that both complexes display dual emission from MLCT and LLCT excited states. Abstract : Herein we describe the DNA binding properties of two new water-soluble ruthenium complexes; experimental and computational data reveal that both complexes display dual emission from MLCT and LLCT excited states. The interaction of the new complexes with DNA was also investigated. Although one of the complexes only binds DNA though groove binding, the second complex has separate ligands capable of groove binding and intercalation. Nevertheless, it was found that both complexes interact with duplex DNA with high affinity. DNA induced distinctive changes in the emission of the complexes; although the groove binding complex only displays a modest increase in emission on binding, the complex that contains the intercalating Ru II (dppz) moiety displays a large increase in MLCT-based emission on DNA binding while emission from the LLCT excited state is unaffected. This means that the complex functions as the first ratiometric sensor for DNA.